Optimalisasi digital perbankan syariah dalam menghadapi tantangan dan peluang - Fadhilah, Moh Nur (Maliki Interdisciplinary Journal, 2025)
There are many opportunities and challenges for Sharia Banks in Indonesia in today's digital world. With the rapid development of technology, Islamic banks can take advantage of digitalization to increase operational efficiency and expand market access. These opportunities include growing public trust, especially the younger generation who are more technologically literate and want faster and more convenient services. But there are also significant challenges, including the need for human resources skilled in technology, cybersecurity and strong customer support. Apart from that, Islamic banks have to compete with conventional banks which have more digital infrastructure and problems in several areas such as slow internet connections. Digital wallets offer better, more accessible services, meet the increasingly complex and mobile expectations of society, and utilize new technologies, while reducing operational costs so that Islamic banks can focus on developing online banking services without geographical limitations. including mobile banking, SMS banking, mobile banking and internet banking, customers can access banking services without geographical limitations, including mobile banking, SMS banking, mobile banking and online banking, with various levels of financial and digital literacy across the country.